How to Equity Ratio, Profitability and Firm Value Shape Stock Prices: An In-Depth Analysis - Paramitra, Yuaniko (Research of Accounting and Governance, 2024)
This research aims to determine the effect of the Debt-to-Equity Ratio, Earning Per Share, and Price Earning Ratio on the share price. This research uses a quantitative approach with secondary data obtained from financial reports for the period 2015 to 2019. The research results show that simultaneously, the variables DER, EPS, and PER have a significant influence on stock prices. Partially, the DER and EPS variables have a weak influence on stock prices, while PER has a stronger influence on share prices. This finding has the implication that company management must consider these financial factors in their share price increase strategy. It is hoped that this research can contribute to financial literature and become a reference for further research. The contribution of this research to the finance literature is significant in several ways. First, this research highlights the influence of the Debt-to-Equity Ratio (DER), Earning Per Share (EPS), and Price Earning Ratio (PER) on the share price of PT Agung Podomoro Land Tbk from 2015 to 2019. Managerial Implications The study examining the effect of Debt-to-Equity Ratio, Earning Per Share, and Price Earning Ratio on stock prices provides critical insights for corporate financial managers and investors.